A basic mathematical testbed for energy efficiency analyses of DC power distribution systems/microgrids - Faizan Dastgeer; Hafiz Muhammad Anees; Hasan Erteza Gelani; Kashif Amjad; Rameez Arif (Institute of Advanced Engineering and Science, 2021)
DC power distribution has become a topic of interest in the recent past, despite being given up a long time. A number of research efforts have been carried out in this field; especially the idea of DC distribution for microgrids has witnessed a significant amount of time and attention. System efficiency is one of the under-research areas of this field that has witnessed a lot of research efforts which were generally simulation based studies. Detailed mathematical efficiency analysis is missing in the present body of knowledge. In this regard, the current research effort aims to present a foundation level mathematical efficiency analysis set-up that may be used as an analytical testbed for different efficiency studies especially those related to the comparative evaluation of DC and AC systems. The current effort highlights the strong dependence of AC and DC distribution system efficiency on the factor of time. The efficiency advantage of DC over AC or vice versa within a specified duration depends on the ratio of DC and AC grid powers summed over the duration.